Choroba przewlekła jako przeszkoda w osiąganiu niezależności u dzieci (dokument dostępny po zalogowaniu tylko dla osób z dysfunkcją wzroku) - Konieczna, Iwona (Warszawa: Akademia Pedagogiki Specjalnej im. Marii Grzegorzewskiej)
Chronic diseases determine children`s functioning in different areas of their life. It is caused very often by unclear experiences which are result of typical disease unit (such as physical pain, activity restriction), impact into environment (feeling of danger, fear, physical suffering).
Keywords: choroba przewlekła; dziecko z chorobą przewlekłą; samodzielność; chronic disease; self - reliance; independence; child with chronic disease